Tailoring Biologic or Immunomodulator Treatment Withdrawal in Inflammatory Bowel Disease - Louis, Edouard (Frontiers in Medicine, 2020)
There is currently no cure for inflammatory bowel disease. Most recent treatments and treatment strategies allow to heal intestinal lesions and maintain steroid-free remission in a subset of patients. These patients and their doctors often ask themselves whether the treatment could be withdrawn. Several studies in both Crohn’s disease and ulcerative colitis have demonstrated a risk of relapse which varies between 20 and 50% at one year and between 50 and 80% beyond 5 years. These numbers clearly highlight that stopping therapy should not be a systematically proposed strategy in those remitting patients. Nevertheless, they also indicate that a minority of patients may not relapse over mid-term and that those who have relapsed may have benefited from a drug-free period before being again treated for a new cycle of treatment. In this context, it would be good to optimally select the patients, candidates for a successful treatment withdrawal. The criteria impacting this decision are: the risk of relapse (linked to factors like mucosal healing and biomarkers), the consequence of a potential relapse, the tolerance and potential side effects of therapy, patients’ priorities and preferences, and the costs. Integration of these parameters allow to propose a decisional algorithm that may help the patients and doctors to make an appropriate decision for their individual case.